Semilunar Coronally Repositioned Flap for the Treatment of Gingival Recession with and without Tissue Adhesives: A Pilot Study - M. Jahangirnezhad (Tehran University of Medical Sciences, 2006)
Statement of problem: One of the main goals in periodontal therapy is the correction of recession defects; therefore the efficacy and predictability of the various techniques are important considerations for clinicians. Purpose: The purpose of this pilot study was to compare the outcomes of gingival recession therapy using the semilunar coronally repositioned flap (SCRF) alone and in conjunction with a tissue adhesive (EPIGLU). Materials and Methods: Thirty-two anterior and premolar teeth with class I and II Miller gingival recessions were selected and randomly divided into two groups. The test group received SCRF followed by EPIGLU application and the control group was managed with SCRF alone. Clinical parameters measured at baseline and 7, 14, 30 and 90 days after surgery included vertical and horizontal recession depths, width of keratinized tissue, probing depth, clinical attachment level, percentage of root coverage, and sensitivity of root surface to air flow. Results: The recession depths decreased significantly in both groups (P